Profitability Driving Factors Of Property Developers In Malaysia - Wong, Wee Chez (2022)
Property developers has been enjoying a good profit margin when property market in Malaysia experiencing market boom after 2009, until it reached its peak at between 2011 to 2012, then the number of property transactions has steadily declined. Despite the property market is a cyclical business, the determinant of developer’s profitability depends on how they react to business environment. Therefore, an assessment is on the profitability during factor of property developer in Malaysia is carried out. The questionnaire was used to collect the data with total respondents of 73 in Klang Valley and analyzed using descriptive and correlation analysis. The result obtained show there are about total 16 profitability factors. Besides, the relationship between financial competency and performance and developer’s profit shows positively correlated. Hence, there is a need for developers to study the areas to maintain their profitability. Suggestions are given on the housing delivery and policy system to maintain the sustainability, survivability, profitability of property developer. Future researchers are recommended to expand this study on project design and project location that are profitable for property developer.